HUKUM PERKAWINAN DI TIMUR TENGAH - Rasyid Siddiq; Sukiati; Iwan (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study examines marriage law in Middle Eastern countries, focusing on the legal basis, regulations, and dynamics of family law reform in several key countries, including Egypt, Saudi Arabia, Jordan, and Tunisia. This study uses normative legal methods with legislative, conceptual, and comparative approaches to examine how Islamic law is implemented in each country's national legal system. The results show that although Middle Eastern countries share the same normative sources, namely the Qur'an, Hadith, and Islamic jurisprudence, in practice there are significant differences in the form of codification, implementation, and level of marriage law reform. Egypt and Jordan tend to develop moderate family law systems with a codification approach and selection of school opinions (takhayyur), while Saudi Arabia still displays a conservative character based on the Hanbali school of law despite starting to implement legal reforms. On the other hand, Tunisia is the most progressive country, having implemented major reforms in family law, including restrictions on polygamy and strengthening women's rights in divorce. These differences indicate a broad legal spectrum in the marriage legal system in the Middle East, ranging from conservative to progressive. This study concludes that marriage law in the Middle East is dynamic and adaptive to social change, without relinquishing the legitimacy of Islamic law as the primary source of law. Therefore, marriage law in this region reflects the interaction between classical Islamic jurisprudence traditions, state policies, and the demands of modernity in shaping family law.